2017
DOI: 10.1080/02687038.2017.1358352
|View full text |Cite
|
Sign up to set email alerts
|

Morphosyntactic production in Greek- and Italian-speaking individuals with probable Alzheimer’s disease: evidence from subject–verb agreement, tense/time reference, and mood

Abstract: Morphosyntactic production in Greek-and Italian-speaking individuals with probable Alzheimer's disease: Evidence from subject-verb agreement, tense/time reference, and mood Background: In probable Alzheimer's disease (AD) different memory systems, executive functioning, visuospatial recognition, and language are impaired. Regarding the latter, only a few studies have investigated morphosyntactic production thus far. Aims: This study, which is a follow-up on Fyndanis, Manouilidou, Koufou, Karampekios, and Tsapa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 61 publications
4
20
0
Order By: Relevance
“…Interestingly, the PADILIH also accounts for the selective impairment in the use of past and non-past in patients with Alzheimer's disease (AD) and semantic dementia (SD): Irish et al (2016) examined the use of past and present tenses in autobiographical narratives in patients with AD and SD, and found that verbs referring to the past were significantly compromised in both groups, as compared to the healthy speakers. Further, the cross-linguistic (Greek and Italian) individual data from speakers with AD showed a worse performance on past reference than on future reference (Fyndanis et al, 2018b), which is consistent with the PADILIH.…”
Section: Tense Aspect Time Reference and The Padilihsupporting
confidence: 77%
“…Interestingly, the PADILIH also accounts for the selective impairment in the use of past and non-past in patients with Alzheimer's disease (AD) and semantic dementia (SD): Irish et al (2016) examined the use of past and present tenses in autobiographical narratives in patients with AD and SD, and found that verbs referring to the past were significantly compromised in both groups, as compared to the healthy speakers. Further, the cross-linguistic (Greek and Italian) individual data from speakers with AD showed a worse performance on past reference than on future reference (Fyndanis et al, 2018b), which is consistent with the PADILIH.…”
Section: Tense Aspect Time Reference and The Padilihsupporting
confidence: 77%
“…This study investigates verb-related morphosyntactic abilities in MS focusing on Greek, a highly inflected language. Recent evidence suggests that, contrary to what was long believed, verb-related morphosyntactic production can be selectively impaired in neurodegenerative disorders such as Alzheimer's disease (AD) (e.g., 2018b). For instance, found that, in Greek AD, Aspect is more impaired than Time Reference/Tense and subject-verb Agreement, and Time Reference is more impaired than Agreement.…”
Section: Introductionmentioning
confidence: 95%
“…6 The view that integration processes are demanding in terms of processing resources (and, thus, challenging for persons with agrammatic aphasia) is shared (explicitly or implicitly) by several scholars (e.g., Avrutin, 2000;Bastiaanse et al, 2011;Hartsuiker et al, 1999;Kok et al, 2007;Yarbay Duman & Bastiaanse, 2009). Although the IFIH gained further empirical support by a recent study on Greek aphasia and healthy aging , Fyndanis, Arfani et al (2018), based on cross-linguistic data from Alzheimer's disease, revised the IFIH suggesting that "morphosyntactic categories that involve integration processes are harder to process than those that do not, unless they are instantiated through free-standing morphemes" (p. 22).…”
Section: The Distinction Between Interpretable and Uninterpretable Fementioning
confidence: 99%